Reforming the Indonesian Bureaucracy through State Civil Apparatus Reform, Could It be Optimized with Technology? - Amancik Amancik; Sonia Ivana Barus; Putra Perdana Ahmad Saifulloh; Novendri M. Nggilu; Asrul Ibrahim Nur (Journal of Law and Legal Reform, 2024)
Bureaucracy, from a societal perspective, is often perceived as complex, slow, and inefficient. Despite these criticisms, bureaucracy remains a fundamental component of governance and plays a crucial role in societal functioning. As such, bureaucratic reform has been a prominent focus of policy discussions for several decades. A technology-driven government system, coupled with a bottom-up approach, has the potential to enhance efficiency, transparency, and accountability in public administration. However, in practice, such reforms have been largely confined to central government institutions and select agencies. This study aims to explore the integration of technology within the bureaucratic system in Indonesia, with a focus on its comprehensive implementation across government structures. Employing a normative research methodology, the study emphasizes the need for the government to take proactive steps in developing a skilled workforce in information technology. The authors also recommend strategically mapping positions that can integrate technological expertise throughout government departments. Furthermore, the study proposes a comprehensive examination of the potential for replacing executive positions with artificial intelligence (AI) to streamline and simplify bureaucratic processes.  In addition to technological advancements, bureaucratic reform must be accompanied by legal reform, particularly in the areas of data security and the protection of personal information. This includes redefining bureaucratic and personal data categories to ensure robust safeguards. The Personal Data Protection Law should play a pivotal role in integrating these data types and ensuring their protection. Moreover, the Telecommunications Act and the Personal Data Protection Act should foster collaboration between the government and technology companies to develop effective security solutions. Lastly, strengthening the Ombudsman as a public service oversight institution is essential to ensuring transparency and accountability in the implementation of bureaucratic and technological reforms.